P.016 Bimanual psychomotor performance in neurosurgical resident applicants assessed using NeuroVR (formerly NeuroTouch), a virtual reality simulator. (17th June 2016) - Winkler-Schwartz, A; Bajunaid, K; Mullah, M; Marwa, I; Alotaibi, F; Baggiani, M; Azarnoush, H; Al Zharni, G; Christie, S; Sabbagh, A; Werthner, P; Del Maestro, R; et al.
Abstract : Background: Current selection methods for neurosurgical residents lack objective measurements of psychomotor performance. This pilot study was designed to answer three questions: 1) What are the differences in bimanual psychomotor performance among neurosurgical residency applicants using the NeuroVR (formerly NeuroTouch) neurosurgical simulator? 2) Are there exceptionally skilled medical student applicants? 3) Does previous surgical exposure influence surgical performance? Methods: Medical students attending neurosurgery residency interviews at McGill University were asked to participate. Participants were instructed to remove 3 simulated brain tumors. Validated tier 1, tier 2, and advanced tier 2 metrics were utilized to assess bimanual psychomotor performance. Demographic data included weeks of neurosurgical elective and prior operative exposure. Results: Sixteen of 17 neurosurgical applicants (94%) participated. Performances clustered in definable top, middle, and bottom groups with significant differences for all metrics. Increased time spent playing music, increase applicant self-evaluated technical skills, high self-ratings of confidence and increased skin closures statistically influenced performance on univariate analysis. A trend for both self-rated increased operating room confidence and increased weeks of neurosurgical exposure to increase blood loss was seen in multivariate analysis. Conclusions: Simulation technology identifies neurosurgical residency applicants at the extremes of technical ability and extrinsic and intrinsic applicant factors appear to influence performance.